A numerical approach for the analysis of deformable journal bearings - D. Benasciutti; M. Gallina; M. Gh. Munteanu; F. Flumian (Fracture and Structural Integrity)
This paper presents a numerical approach for the analysis of hydrodynamic radial journal bearings. The effect of shaft and housing elastic deformation on pressure distribution within oil film is investigated. An iterative algorithm that couples Reynolds equation with a plane finite elements structural model is solved. Temperature and pressure effects on viscosity are also included with the Vogel-Barus model. The deformed lubrication gap and the overall stress state were calculated. Numerical results are presented with reference to a typical journal bearing configuration at two different inlet oil temperatures. Obtained results show the great influence of elastic deformation of bearing components on oil pressure distribution, compared with results for ideally rigid components obtained by Raimondi and Boyd solution.